Report on species of the genus Tumicla Wallengren, 1863 in Gabon (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Durante, Antonio; Apinda-Legnouo, Emelie Arlette (Zootaxa, 2020)
The Tumicla species of Gabon are reviewed and eight new species described: Tumicla bongorum n. sp., Tumicla falcata n. sp., Tumicla globosa n. sp., Tumicla latipunctata n. sp., Tumicla minima n. sp., Tumicla pallida n. sp., Tumicla parvipunctata n. sp. and Tumicla whitensis n. sp. A key and an updated checklist of world Tumicla are also provided.